Fibroblast Growth Factor 12 Is a Novel Regulator of Vascular Smooth Muscle Cell Plasticity and Fate. Issue 9 (September 2016) - Song, Sun-Hwa; Kim, Kyungjong; Jo, Eun-Kyung; Kim, Young-Wook; Kwon, Jin-Sook; Bae, Sun Sik; Sung, Jong-Hyuk; Park, Sang Gyu; Kim, Jee Taek; Suh, Wonhee
Abstract : Objective—: Vascular smooth muscle cells (VSMCs) modulate their phenotype between synthetic and contractile states in response to environmental changes; this modulation plays a crucial role in the pathogenesis of restenosis and atherosclerosis. Here, we identified fibroblast growth factor 12 (FGF12) as a novel key regulator of the VSMC phenotype switch. Approach and Results—: Using murine models and human specimens, we found that FGF12 was highly expressed in contractile VSMCs of normal vessel walls but was downregulated in synthetic VSMCs from injured and atherosclerotic vessels. In human VSMCs, FGF12 expression was inhibited at the transcriptional level by platelet-derived growth factor-BB. Gain- and loss-of-function experiments showed that FGF12 was both necessary and sufficient for inducing and maintaining the quiescent and contractile phenotypes of VSMCs. FGF12 inhibited cell proliferation through the p53 pathway and upregulated the key factors involved in VSMC lineage differentiation, such as myocardin and serum response factor. Such FGF12-induced phenotypic change was mediated by the p38 MAPK (mitogen-activated protein kinase) pathway. Moreover, FGF12 promoted the differentiation of mouse embryonic stem cells and the transdifferentiation of human dermal fibroblasts into SMC-like cells. Furthermore, adenoviral infection of FGF12 substantially decreased neointima hyperplasia in a rat carotid artery injury model. Conclusions—: In general, FGF family members induce a synthetic VSMC phenotype. Interestingly, the present study showed the unanticipated finding that FGF12 belonging to FGF family, strongly induced the quiescent and contractile VSMC phenotypes and directly promoted VSMC lineage differentiation. These novel findings suggested that FGF12 could be a new therapeutic target for treating restenosis and atherosclerosis. Abstract : Supplemental Digital Content is available in the text.